Cutting forces and temperature measurements in cryogenic assisted turning of AA2024-T351 alloy: An experimentally validated simulation approach. (January 2022) - Gupta, Munish Kumar; Korkmaz, Mehmet Erdi; Sarıkaya, Murat; Krolczyk, Grzegorz M.; Günay, Mustafa; Wojciechowski, Szymon
Highlights: FEM simulation of cutting forces and cutting temperature were performed. Advantedge software was used for FEM simulation. Experiments were performed to validate the results. Abstract: Aluminium alloys are widely used in modern engineering applications such as automobile, aerospace etc because of its characteristics. The machining of aluminium alloys are also considered as difficult because of its sticky and soft nature, low thermal conductivity, strain hardening effect etc. The cooling conditions employed at cutting zone improved the machining performance but the resources, material consumption, skilled labor etc. are also required for performing the machining experiments. Therefore, the simulation of process parameters with the help of Finite Element Modelling (FEM) during machining is highly researched topic these days. In this work, a new practice from measurement science i.e., FEM simulation was performed with AdvantEdge software and the prediction models were developed for evaluating the cutting forces and cutting temperature while machining AA2024-T351 alloy under dry, liquid nitrogen (LN2 ) and carbon dioxide (CO2 ) conditions. Initially, the 3D turning model was developed and the results were compared with experimental findings. The results obtained from simulation model are very close with experimental results with minimum standard value of 0.67 (5.7%) for cutting forces and 4.58 (6.16%) for cutting temperature. Thus, it is worthy to mention that the 3D FE model is efficient and effective to predict and measurement results with minimum error.